A Quality of Sleep and Factors Affecting Sleep among Nurses: A Cross-sectional Study - Chaudhari, Jyoti (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: To find the quality of sleep and factors affecting sleep among nurses working in shifts. Introduction: The sleep is a fundamental right and physiological need of the body. However, having adequate and quality of sleep is more important for work efficiency. Nurses being the health care provider who provides services round o’clock to the patient requires quality sleep. Methods: This investigation was cross-sectional. Data are obtained thrice, once after each shift from 30 nurses working in the selected hospital utilizing the pittsburgh sleep quality index (PSQI), to assess quality of sleep and the researcher made a Likert scale to assess perceived factors affecting their sleep. A lower score of PSQI on a range of 0–21 indicates better sleep quality. Results: The mean age of nurses was 24 years and only 20% of nurses were married. About 50 % of the participating nurses had more than 2 years of experience. Two third of nurses were working in ICU. The nurses’ overall PSQI score was found better during the evening shift (PSQI score 5) than the morning (PSQI score 5.8) and night (PSQI score 7.6). Factors such as child-rearing activities, educational requirements, daily activities, and food intake are more seen in the morning shift whereas mental stress, the workload at home, and environmental factors are seen more in night shifts. Conclusion: Nurses experienced better sleep during the evening shift, highlighting the importance of managing factors like child-rearing activities and mental stress for improved sleep quality